A Web-Based Medical Appointment Scheduling with SMS Alert Notification System - Ele, Bassey; J. A., Odey; N. E., Frank; I. M., Ekinya (Transactions on Engineering and Computing Sciences, 2020)
Lengthy waiting times for registering and booking an appointment to see a doctor is challenging in Nigeria, particularly in government hospitals. Also, missed healthcare appointments are the main cause of preventable incompetence that affects a patient’s wellbeing and medication results, as there is no machinery to notice patients when appointments are deferred or canceled. To address these issues, a web-based medical appointment scheduling system with SMS alert notification using the University of Calabar Teaching Hospital (UCTH) as a case study is proposed. This study adopted the Structured System Analysis and Design Methodology in the development of the system. MySQL was used to design the database for this study and the proposed system was implemented using PHP programming language. A web-based medical appointment scheduling with an SMS alert notification system was developed and implemented in this study. The developed system will improve appointment scheduling in hospitals to simplify patients' and doctors’ tasks and eliminate missed appointments with the help of the reminder component. In the upcoming, the system can be developed to direct appointment applications to another hospital where doctors with similar medical proficiency are working. Furthermore, the provision of automated SMS alerts as notifications as the appointed day draws near or reaches is a fundamental characteristic of the developed system.